2008
DOI: 10.1029/2007gl032764
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of downward leader in a positive cloud‐to‐ground lightning flash observed by high‐speed video camera and electric field changes

Abstract: Leader process in a positive single‐stroke cloud‐to‐ground lightning flash was captured by a high‐speed video camera with a time resolution of 1000 frames/s. The positive leader process and the intracloud discharge process before the return stroke, which lasted about 600 ms, are studied in detail by combining the data from fast and slow antenna. The channel branches seemed to develop horizontally with a speed of the order of 104 m/s during the initial stage just outside the thundercloud. The luminous duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 16 publications
9
80
2
Order By: Relevance
“…However, electric field measurements showed that positive flashes are sometimes preceded by pronounced intracloud discharge lasting 100-200 ms, rather than the preliminary breakdown process [Rust et al, 1981;Fuquay, 1982]. Optical records confirmed that positive CG flashes can be initiated from a channel branch of intracloud discharge [Kong et al, 2008;Saba et al, 2009], and the weak preliminarily breakdown process is replaced by IC discharge in this case.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, electric field measurements showed that positive flashes are sometimes preceded by pronounced intracloud discharge lasting 100-200 ms, rather than the preliminary breakdown process [Rust et al, 1981;Fuquay, 1982]. Optical records confirmed that positive CG flashes can be initiated from a channel branch of intracloud discharge [Kong et al, 2008;Saba et al, 2009], and the weak preliminarily breakdown process is replaced by IC discharge in this case.…”
Section: Introductionmentioning
confidence: 62%
“…[28] Rakov [2003] suggested that +CG flashes might be generated by intracloud lightning that extends horizontally. The optical observation and lightning mapping results with very high frequency (VHF) imaging also proved that some channels of intracloud lightning can produce +CG strokes [Kong et al, 2008;Saba et al, 2009;Lu et al, 2013]. Saba et al [2009] found that leaders with both polarities might trigger positive CG strokes.…”
Section: Morphologies Of Positive Cg Flashes Accompanied By Ic Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, S10 also reported that some 1CG strokes produced a new ground contact while the CC from a previous stroke was still in progress. Positive downward leaders also can be initiated by the CC phase of IC discharges (e.g., Kong et al 2008). S10 concluded that the spatial and temporal criteria presently used to group 2CG strokes into flashes may not be valid for 1CG, and that the very concept of a lightning flash being a group of strokes that are collocated in space and time should be reconsidered for 1CG.…”
Section: B Cloud-to-ground Characteristicsmentioning
confidence: 99%
“…These lightnings occur in the troposphere and have been extensively studied [1][2][3][4][5][6][7][8][9][10][11]. However, there are another type of lightning discharges which occur above the thunderstorms, with the top altitude even reaching the ionosphere.…”
mentioning
confidence: 99%